2019
DOI: 10.1016/j.tig.2019.04.008
|View full text |Cite
|
Sign up to set email alerts
|

The Pregnancy Pickle: Evolved Immune Compensation Due to Pregnancy Underlies Sex Differences in Human Diseases

Abstract: We hypothesize that, ancestrally, sex-specific immune modulation evolved to facilitate survival of the pregnant person in the presence of an invasive placenta and an immunologically challenging pregnancy; an idea we term the Pregnancy Compensation Hypothesis. Further, we propose sex differences in immune function are mediated, at least in part, by the evolution of gene content and dosage on the sex chromosomes, and regulated by reproductive hormones. Finally, we propose that changes in reproductive ecology in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
136
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(141 citation statements)
references
References 85 publications
5
136
0
Order By: Relevance
“…The 'pregnancy-compensation hypothesis' (70) suggests that women's immune system ramps up throughout adulthood to prepare for a sequence of pregnancies, as from an evolutionary perspective and before birth control, the majority of women would have been pregnant for many of their adult years. According to Natri and colleagues, problems may arise when the 'expected' pregnancies fail to occur; without a frequent push-back from pregnancy-related mechanisms, the immune system can become overly elevated and start releasing auto-antibodies that attack healthy cells (70). Positive effects of parity on the brain may thus reflect mechanisms related to immune factors rather than estrogen fluctuations involved in pregnancy (40).…”
Section: Discussionmentioning
confidence: 99%
“…The 'pregnancy-compensation hypothesis' (70) suggests that women's immune system ramps up throughout adulthood to prepare for a sequence of pregnancies, as from an evolutionary perspective and before birth control, the majority of women would have been pregnant for many of their adult years. According to Natri and colleagues, problems may arise when the 'expected' pregnancies fail to occur; without a frequent push-back from pregnancy-related mechanisms, the immune system can become overly elevated and start releasing auto-antibodies that attack healthy cells (70). Positive effects of parity on the brain may thus reflect mechanisms related to immune factors rather than estrogen fluctuations involved in pregnancy (40).…”
Section: Discussionmentioning
confidence: 99%
“…Most women do not manifest X-linked disorders because (1) they are not homozygous for the pathogenic variant, and (2) their variant cells (those expressing the deleterious allele) receive sufficient gene product to carry out the essential metabolic function from the cells that transcribe the normal allele.…”
Section: Females Can Ameliorate the Effects Of Pathogenic Variantsmentioning
confidence: 99%
“…Sex differences in human disease are usually attributed to sex specific life experiences, and sex hormones that influence the function of susceptible genes throughout the genome. [1][2][3][4][5] Such factors do account for some dissimilarities. However, a major cause of sex-determined expression of disease has to do with differences in how males and females transcribe their gene-rich human X chromosomes, which is often underappreciated as a cause of sex differences in disease.…”
Section: Introductionmentioning
confidence: 99%
“…When further investigation revealed that the only known function or disease was related with the immune system, and there were no arguments to be assigned to another system, the genes were annotated as ISRG, e.g. CXorf21 [33], DOCK11 [34], GAB3 [35] (Additional file 3). All these were confirmed by the GO approach.…”
Section: Discussionmentioning
confidence: 99%